A Review of Research on Women’s Use of Violence With Male Intimate Partners - Swan, Suzanne C. (2008)
This article provides a review of research literature on women who use violence with intimate partners. The central purpose is to inform service providers in the military and civilian communities who work with domestically violent women. The major points of this review are as follows: (a) women’s violence usually occurs in the context of violence against them by their male partners; (b) in general, women and men perpetrate equivalent levels of physical and psychological aggression, but evidence suggests that men perpetrate sexual abuse, coercive control, and stalking more frequently than women and that women also are much more frequently injured during domestic violence incidents; (c) women and men are equally likely to initiate physical violence in relationships involving less serious “situational couple violence,” and in relationships in which serious and very violent “intimate terrorism” occurs, men are much more likely to be perpetrators and women victims; (d) women’s physical violence is more likely than men’s violence to be motivated by self-defense and fear, whereas men’s physical violence is more likely than women’s to be driven by control motives; (e) studies of couples in mutually violent relationships find more negative effects for women than for men; and (f ) because of the many differences in behaviors and motivations between women’s and men’s violence, interventions based on male models of partner violence are likely not effective for many women.